Analysis of the use solar cells in cultivation automatic hydroponic plant based arduino uno microcontroller - Fauziah Hanum Simbolon; Siti Anisah; Solly Aryza (Sean Institute, 2024)
Hydroponics is a form of plant cultivation that is widely used without using soil and has several circulation systems such as (Deep Flow Technique) DFT and (Nutrient Film Technique) NFT. This research describes one solution to improve the weaknesses of manual hydroponics, especially in terms of circulating nutrient fluids and using pumps. Hydroponic farmers tend to circulate nutrient fluids using pumps that operate 24 hours continuously, whose electricity is supplied by PLN. In addition, the pump remains on continuously for 24 hours, which can shorten the life of the pump. This hydroponic design uses a DFT hydroponic system equipped with a DS18B20 sensor which can measure the volume of nutrient fluid, a water level sensor and also measure the temperature of the nutrient fluid in the hydroponic pipe. The electrical power to drive the pump comes from solar heat produced by solar panels. Here the relay sensor, water level sensor and assisted by a water flow sensor and DS18B20 sensor as the main key in the nutrient fluid circulation process in hydroponic plants are assisted by a 12V DC pump and all of this cannot be separated from the control system used to check sensor performance, namely the Arduino Microcontroller system.